Analisis Praktik Pelaporan Keuangan Masjid sebagai Organisasi Nirlaba Berdasarkan ISAK 335 dalam Akuntansi Sektor Publik - Diva Fadillah Ramika; Faradilla Raudha Azievan; Dhea Sabrina Putri; Ahmad Valevi; Muhammad Yazid; Cindy Arya Zona; Jeni Sopianti; Sri Adella Fitri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
As nonprofit organizations, mosques play a vital role in managing community funds, making clear and accountable financial management essential. This study aims to analyze the implementation of public sector accounting and financial reporting in accordance with ISAK 335 at the Ihsan Mosque in Batusangkar, the Ishlah Mosque in Pariangan, and the Baburrahim Mosque in Batu Basa. The method used in this study is qualitative descriptive through observation, interviews, and document collection. The results show that all three mosques still use simple record-keeping, consisting of cash receipts and disbursements, and have not yet adopted ISAK 335. Some obstacles encountered include a lack of human resources, the absence of financial audits, and administrative systems that remain conventional. Nevertheless, the mosques have additional sources of income, such as the rental of shop houses and the management of agricultural land, to support community worship and social activities. This study concludes that the implementation of ISAK 335 is essential to create more transparent, accountable, and professional mosque financial management.